5PSQ-020 Reducing time and potential errors in cpr medications using a cpr calculator in paediatric wards. (2nd March 2018) - Almeziny, M; Fan, I; Binobaid, S
Abstract : Background: Medication errors are the most common cause of untoward events affecting patients, especially in paediatric patients. Moreover, the CardioPulmonary Resuscitation (CPR) process is very prone to errors. as it is characterised by a combination of urgency, time constraints and mental stress, with the need to perform occasionally complex calculations and not always being able to double-check figures prior to applying the ordered medications. The Institute for Safe Medication Practices (ISMP) recommended Computerised Provider Order Entry (CPOE) as a tool that could reduce errors combined with the Clinical Decision Support System (CDSS). Purpose: The purpose of this study is to present a computer based CPR calculator as a safer and faster method for CPR calculation than manual calculation. This project is to replace the existing paper-based CPR card with a CPR calculator combined with CDSS. Material and methods: Setting: tertiary hospital. Population: all admitted paediatric patients. Method: a group of 70 nurses were randomly selected to calculate manually a CPR card and then enter the patient data into the CPR calculator. The time that is needed to complete the manual calculations and the time that is needed to enter patient information into the CPR calculator were measured. In addition, the number of medication calculation errors were recorded. Results: The average time to finish the CPR card manually was 00:08:31 min and the average time to generate the CPR card using the CPR calculator was 00:01:15 (p<0.05). The number of nurses who made errors in manual calculations was 23, the total number of errors was 101 (p<0.05). There were no errors with the calculator. Conclusion: The electronic CPR calculator has provided an accurate method with no errors and a faster way of generating CPR medications compared to the manual method. References and/or Acknowledgements: 1. Agency NPS. Seven steps to patient safety: the full reference guide 2004. National Patient Safety Agency. 2. Courtenay M, Griffiths M. Medication safety: an essential guide 2009. Cambridge University Press. 3. Ernst FR, Grizzle AJ. Drug-related morbidity and mortality: updating the cost-of-illness model. J Am Pharm Assoc2001;41(2):192–199. doi:10.1016/S1086-5802(16)31229-3 No conflict of interest